PELATIHAN DAN PENDAMPINGAN PEMBUATAN KOMPOS MENGGUNAKAN LUBANG RESAPAN BIOPORI (LRB) DENGAN ALAT SEDERHANA DALAM RANGKA PEMANFAATAN SAMPAH ORGANIK - Siti Indriyati Idris; Nurlaili Dwi Ulfah; Reski Kartini Addas (Sekolah Tinggi Ilmu Ekonomi AMA, 2022)
The amount of waste is not balanced between disposal and processing. It caused garbage accumulated. In addition, limitation of land and lack of understanding in managing waste, which is mostly organic waste or household waste, contributes to amount of waste production. The solution to this problem is to make biopore infiltration holes. It is one method that is easy and can be applied by all people. The purpose of this activity is to provide training and assistance to students of MAS Madani Alauddin Pao-Pao as biopore cadres in making compost using Biopore infiltration holes. As result of this activity, the cadres have been able to utilize organic waste to make compost by using biopore. The biopore infiltration holes that have been made can be minimize flooding and improve soil structure and make plants more fertile.